Systemic functional grammar: a tool to investigate the lexicogrammatical complexification of advanced portuguese-efl interlanguage - Pedro H. L. Praxedes Filho (Ilha do Desterro)
Very few longitudinal studies have been conducted on classroom Second Language Development, aiming at revealing the lexicogrammatical characteristics of the simplification-complexification continuum of the different L2 interlanguage stages in an instructed setting. The objective of this study is to investigate the level of lexicogrammatical complexification of the Portuguese-English interlanguage of advanced learners. It is intended as a pilot cross-sectional study to verify the suitability of systemic functional grammar (SFG) as a data categorization framework. Ten English-as-a- Foreign-Language students from two universities in the state of Ceará, Brazil, were the subjects who provided the data: spoken and written narratives. Based on SFG, the narratives were segmented into ranking clauses and analyzed for the configurational functions that realize the systems of transitivity and mood. The narratives would be considered to bear a high level of complexification if they had more than 80% of complete clauses in terms of transitivity and mood configurational functions. The hypothesis that the spoken and written narratives would have a high level of complexification separately (87.61% and 94.14%) and together (90.72%) was confirmed, and so was the hypothesis that the written narratives would present an even higher level. Although SFG proved to be suitable for the investigation of lexicogrammatical complexification at the advanced level, it is recommended that other cross-sectional studies be carried out with learners at beginning and intermediate levels.